2017
DOI: 10.1038/s41598-017-17974-y
|View full text |Cite
|
Sign up to set email alerts
|

Tunable two-phonon higher-order sideband amplification in a quadratically coupled optomechanical system

Abstract: We propose an efficient scheme for the controllable amplification of two-phonon higher-order sidebands in a quadratically coupled optomechanical system. In this scheme, a strong control field and a weak probe pulse are injected into the cavity, and the membrane located at the middle position of the cavity is driven resonantly by a weak coherent mechanical pump. Beyond the conventional linearized approximation, we derive analytical expressions for the output transmission of probe pulse and the amplitude of seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 49 publications
1
22
0
Order By: Relevance
“…It is easily seen that in the regime of large optical frequency ω >> Ω, we get β ≈ 0 and the non-standard term vanishes. This is what has actually been probed in nearly all experiments on quadratic optomechanical interactions so far [18][19][20][21][22][23][24]36]. The large mechanical frequency regime of standard quadratic interactions has been however recently probed [25] and it has been suggested that the roles of optical and mechanical parts are expected to interchange without consideration of the non-standard quadratic effect.…”
Section: Hamiltonianmentioning
confidence: 79%
See 1 more Smart Citation
“…It is easily seen that in the regime of large optical frequency ω >> Ω, we get β ≈ 0 and the non-standard term vanishes. This is what has actually been probed in nearly all experiments on quadratic optomechanical interactions so far [18][19][20][21][22][23][24]36]. The large mechanical frequency regime of standard quadratic interactions has been however recently probed [25] and it has been suggested that the roles of optical and mechanical parts are expected to interchange without consideration of the non-standard quadratic effect.…”
Section: Hamiltonianmentioning
confidence: 79%
“…Higher-order operators have been already used in analysis of nonlinear standard optomechanics [35], where its application has uncovered effects known as sideband inequivalence, quantities such as coherent phonon population, as well as corrections to the optomechanical spring effect, zero-point field optomechanical interactions, and a minimal basis with the highest-order which allows exact integration of optomechanical Hamiltonian subject to multiplicative noise input. Also, it has been independently used [36] for investigation of quadratic effects. But this method has not been verified yet for non-standard quadratic optomechanics, which is the central topic of this study.…”
Section: Introductionmentioning
confidence: 99%
“…In experiments, mechanical driving field has been exploited to realize electro-optomechanically induced transparency [78], cascaded optical transparency [79], phase-sensitive parametric amplifier [80], injection locking [81], and virtual exceptional points [82]. Recently, optomechanically induced opacity and amplification of two-phonon higher-order sidebands have been studied in a quadratically coupled optomechanical system with mechanical driving [83,84]. It is pointed out that mechanical driving in the quadratically coupled system can be realized by parametrically modulating the spring constant of the membrane at twice the membrane's resonance frequency with an integrated electrical interface [80-83, 85, 86], which generates the mechanical coherence via the two-phonon process.…”
Section: Introductionmentioning
confidence: 99%
“…If the probe field is much weaker than the control field, one can use the perturbation method to get the prominent feature of optomechanically induced transparency. Recently, nonlinear optomechanical dynamics have emerged as an interesting frontier in cavity optomechanics [27][28][29][30]. This emerging subject leads to a variety of high-order OMIT effects due to the intrinsic nonlinear optomechanical interactions [31,32], such as photon-phonon polariton pairs [33] and sideband generations [27,34,35].…”
Section: Introductionmentioning
confidence: 99%